Pengaruh Media Big Book terhadap Kemampuan Mengenal Mitigasi Bencana dan Percaya Diri Anak Usia 5-6 Tahun - Rosida; Nurul Khotimah; Yes Matheos Lasarus Malaikosa; Sri Setyowati (Institut Agama Islam Negeri Madura, 2025)
The purpose of this study is to analyze the influence of the Big Book media on the ability of 5–6-year-old children to understand disaster mitigation and to examine its role in enhancing their self-confidence. This research employs a quantitative experimental approach. The experimental method used in this study is a quasi-experimental design, also known as a pseudo-experimental design. The population of this study consists of all 30 children in group B at TK Syamsul Huda Bulusan, Banyuwangi. The sampling technique used is a saturated sample, meaning that all 30 children in group B at TK Syamsul Huda Bulusan, Banyuwangi, were included as the research sample. Data collection was conducted using observation methods, and data analysis was carried out using the Mann-Whitney U test. The study examines the pretest-posttest scores of both the control and experimental groups. The results indicate that the Big Book media has a positive effect on children's understanding of disaster mitigation and their self-confidence. This finding confirms that interactive learning media, such as the Big Book, have great potential to enhance the learning quality of 5–6-year-old children. Abstrak